Optimization of Supercritical CO2 Natural Dye Extraction from Brown Seaweed (Sargassum Sp.) via Response Surface Methodology - Talib, Nabila; Rozi Ahmad, Mohd; Ismail Ab Kadir, Muhammad; Ismail, Khudzir; Faiz Che Rahim, Ahmad (International Journal of Engineering and Technology, 2018)
This paper discusses the effects of two main parameters (pressure and temperature) in supercritical carbon dioxideextraction of Sargassum sp. through response surface methodology (RSM). Perturbation plot shown significant effects of all process parameters on the yield of extract. An experimental design software was designated to achieve optimization on the process situations pertaining maximum extraction yield. The optimal conditions perceived were at pressure of 4500 psi and temperature of 65Â°C. The highest yield of extract achieved was 2.7 mg-extract/g-dried sample under the optimum conditions. The yield of extract was then further analysed via Gas Chromatography Mass Spectrometry (GCMS) and it was found that Sargassum sp. contains sterols, pentadecanoic acid, 14-methyl ester, 9-Hexadecenoic acid, methyl ester and phytol which are the constituents of bioactive compounds and antimicrobial properties.Â Â